A built-up type horizontally corrugated steel plate shear wall with a special shape. (1st January 2022) - Yu, Yujie; Lin, Siwen; Zhao, Fengtao; Tian, Peifeng; Jiang, Lizhong
Highlights: A built-up type specially shaped corrugated steel shear wall (BS-CSSW) system was proposed. Quasi-static cyclic tests were conducted on two S-CSSW specimens to investigate the shear performance. The BS-CSSW had higher elastic and plastic strength levels, better ductility, slower stiffness reduction. The involvement of interior columns and their positions influence the shear buckling behaviors of corrugated plates. Abstract: A built-up type specially shaped corrugated steel shear wall (BS-CSSW) that can be concealed within enclosure walls was proposed for applications in residential buildings. Quasi-static tests were performed on two specially shaped corrugated steel shear wall specimens (S-CSSW and BS-CSSW) and refined finite element simulations were conducted. With the verified modeling method, a parametric study was performed on BS-CSSWs with different wall configurations and interior column positions. The results indicated that the corrugated shear plates in the S-CSSW underwent premature elastic buckling, thus leading to a sudden drop in strength upon buckling and low strength levels after buckling. Shear panels in the BS-CSSW successfully entered the shear yielding mode and remained in a stable in-plane shearing state until reaching 2% drift. The BS-CSSW had higher elastic and plastic strength levels, better ductility, slower stiffness reduction, lower out-of-plane plate deformation and a wider hysteretic relationship than those of the S-CSSW. The position of the interior columns primarily influenced the slenderness of the side and interior corrugated panels and affected the strength development modes. The BS-CSSWs had separate bearing modes between lateral loads and axial loads and could withstand high axial load conditions with little influence on shear strengths.